DIFFUSION-WEIGHTED MAGNETIC RESONANCE IMAGING IN PEDIATRIC NEURO-ONCOLOGY: ADVANCEMENTS AND APPLICATIONS - Bikram Jeet Singh; R. P. Bansal; Feroz Shaheen (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Pediatric brain tumors constitute a significant cause of morbidity and mortality, requiring accurate diagnosis and grading for optimal treatment planning. Diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) mapping have emerged as valuable tools in neuro-oncology, providing insights into tumor cellularity and aggressiveness.Objective: This study aimed to evaluate the DWI characteristics of pediatric brain tumors and their correlation with tumor grade and classification.Methods: A retrospective analysis of 66 pediatric patients who underwent preoperative DWI was conducted. Tumors were classified as high-grade (WHO grade ≥ III) or low-grade (WHO grade ≤ II) based on histopathology. DWI signal characteristics and ADC values were analyzed to assess their diagnostic accuracy in differentiating tumor grades. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Statistical analysis was performed using SPSS (Version 20), with a significance threshold of p < 0.05.Results: Among 66 tumors, 18 (27.3%) were high-grade, and 48 (72.7%) were low-grade. Diffusion restriction was observed in 77.8% of high-grade tumors but in none of the low-grade tumors. DWI demonstrated a sensitivity of 77.8%, specificity of 100%, PPV of 100%, and NPV of 92.3% for identifying high-grade tumors.Conclusion: DWI and ADC mapping provide valuable non-invasive biomarkers for differentiating pediatric brain tumor grades. Integrating DWI into routine imaging protocols may enhance diagnostic accuracy and guide treatment strategies in pediatric neuro-oncology.